Determinação in situ de fósforo, nitrato e amônio em solo - Menezes, Eveline de Abreu (2006)
The cultures platforms of productivity need to be optimized, owing to provide foods to an enhanced world population. A control of the soil fertility is necessary, in order to be adequately productive without, however, have losses for excess of nutrients, which could cause serious environmental problems. Due to soils and cultures requirements, nitrogen and phosphorus fertilizations are the more important ones. In this work, selective chemical sensors to phosphorus (PO4 3-), nitrate (NO3 -) and ammonium (NH4 +), installed in polymeric probes and their associated instrumentation were evaluated. The evaluation was carried with the addition of 0.1 mol L-1 P-PO4 3- solution to the soil, data acquisition supplied by the probes, collects of soil samples in the region where the probes were installed and determination of evaluated nutrients by conventional laboratory techniques. The PO4 3- amounts were determined by spectrophotometry after the following extraction methodologies: Mehlich-1, Mehlich-3 and ionic exchange resin. The results were compared with the fitted potentials registered by the probes, and the best correlation was obtained with the method of the resin. For evaluation of the probes, constructed with selective sensors to NO3 - and NH4 +, NH4NO3 salt was added directly to the soil. Four probes had been installed; one of them was used as control. Surface and 20-cm soil depth, region where the sensors were located, were periodically collected. The amounts of NO3 - and NH4 + had been determined by spectrophotometry, by using procedure based on Berthlot reaction adapted to a flow system. The results, compared with the potentials provided by the sensors, presented similar changes profiles. Great alterations in the sensors potentials had not been observed after addition of nitrogen fertilization, due to the little percolation of nutrients in the soil profile. The results indicate good response of the sensors, and the potential applicability of these probes to assist the monitoring of soil nutrients, owing the establishment of rational processes in the fertilizers uses by the cultures.